Private sector news, social media distribution, and algorithm change - Cornia, A; Sehl, A; Levy, DAL; Nielsen, RK (Reuters Institute for the Study of Journalism, 2018)
This report examines how private sector legacy news organisations across six European countries use social media for news distribution. It analyses in particular how strategies vary across different news organisations and across platforms, with a section focusing on how publishers have responded to the January 2018 changes to Facebook’s algorithm. Based on 21 interviews with editors and managers at 12 newspapers and commercial broadcasters, the report finds that, even though many news organisations are frustrated by limited direct monetisation and frequent algorithm changes, they still concentrate their resources on Facebook for social media distribution. The impact of the Facebook algorithm change varies across organisations, but is in most cases far from the apocalyptic scenarios anticipated by some commentators. There is no clear pattern to explain this variation, but broadly the organisations that increased their activity on Facebook have seen a smaller decline in interactions than others, and in some cases growth.